Method for preparing silicon borate coated and modified sodium battery positive electrode material by utilizing waste ternary positive electrode material
The waste nickel-cobalt-manganese ternary cathode material is prepared as a sodium-electrode material coated with borosilicate through the short process solid-solid-solid conversion method, which solves the cumbersome recycling process and environmental pollution problems, improves the structural stability and electrochemical performance of the material, and extends the battery life.
Patent Information
- Application Number
- CN202510413940.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-04
AI Technical Summary
The prior art has problems such as cumbersome process, high environmental pollution risk, and inconsistent performance when recycling waste lithium-ion battery positive electrode materials.
The waste nickel-cobalt manganese ternary cathode material is mixed with ammonium sulfate and calcined at high temperature. After leaching lithium, it is mixed with manganese source, sodium source and borosilicate, and sintered at high temperature to form a borosilicate coating layer to form a homogeneous solid melt, which improves the structural stability and electrochemical properties of the material.
It realizes efficient regeneration of waste lithium-ion battery positive electrode materials into high-performance sodium positive electrode materials, shortens the recycling process, reduces environmental pollution, improves the structural stability and electrochemical performance consistency of the material, and extends the battery cycle life.
Smart Images

Figure CN120261790A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of recycling and reuse of waste lithium-ion batteries, and specifically relates to a method for preparing a sodium-ion battery cathode material coated and modified with borosilicate by using waste ternary cathode material. Background Art
[0002] Lithium-ion batteries, with advantages such as high service life and strong energy density, are widely used as superior electrochemical energy storage devices in products such as electric vehicles. However, waste lithium-ion batteries contain a large amount of toxic compounds and valuable metals (such as Li, Ni, Co, etc.). If not properly treated, it will lead to environmental pollution and resource waste. At the same time, the precious metal raw materials required for the production of lithium-ion batteries also face the problem of resource shortage. In contrast, sodium-ion batteries with a working principle similar to that of lithium-ion batteries have advantages such as rich sodium reserves and high economic benefits. Therefore, directly regenerating waste lithium-ion ternary cathode material into a sodium-ion battery cathode material with excellent electrochemical performance has considerable economic and environmental benefits.
[0003] Patent CN116553631A proposes a method for recycling waste lithium-ion battery cathode material to prepare a carbon sodium-ion battery cathode material. This method realizes the effective recycling of waste battery materials and simplifies the recycling process, but there are some limitations. For example, this method involves strong acids and requires extractants for extraction, and the subsequent treatment is relatively cumbersome. At the same time, during the material mixing process, due to the large difference in the physical properties of the materials, the mixing uniformity is poor, which affects the performance consistency of the final product. To overcome these shortcomings, the present invention proposes a method for directly preparing a layered sodium-ion cathode material coated with borosilicate from waste lithium-ion battery cathode with a short process. The whole process of the process does not involve acids and bases, only solid-solid conversion. Shortening the recycling process can also reduce the damage to the environment. At the same time, by utilizing the fluidity characteristics of borosilicate at high temperatures, the reaction is accelerated, ensuring that the materials react fully at high temperatures to form a homogeneous solid solution, thereby improving the structural stability and electrochemical performance consistency of the materials.
[0004] In summary, directly regenerating waste lithium-ion ternary battery cathode material into a sodium-ion battery cathode material coated and modified with borosilicate has great development prospects. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing a sodium-ion battery cathode material coated and modified with borosilicate by using waste ternary cathode material with a short process
[0006] The purpose of the present invention is achieved through the following technical solutions, including the following steps:
[0007] (1) Mix waste nickel-cobalt-manganese ternary cathode with ammonium sulfate in a certain proportion and carry out mechanical ball milling;
[0008] (2) High-temperature calcination is carried out in a tube furnace to obtain a composite material.
[0009] (3) The composite material is subjected to selective water leaching for lithium extraction. After the leaching residue is dried, a transition metal oxide containing a trace amount of remaining lithium is obtained;
[0010] (4) The precursor is mixed with a manganese source, a sodium source, and a silicon borate in a certain proportion, and then mechanically ball-milled for sufficient mixing;
[0011] (5) The precursor is placed in a muffle furnace for high-temperature sintering to obtain a modified sodium-ion battery cathode material with excellent performance.
[0012] Preferably, in step 1, the mass ratio of the waste cathode material to the sulfate is 1:0.5 to 1:0.7.
[0013] Preferably, in step 1, the ball-milling time is 1 to 24 h, and the ball-milling speed is 100 - 800 rpm.
[0014] Preferably, in step 1, the atmosphere in the tube furnace is Ar / H2 or Ar.
[0015] Preferably, in step 1, the calcination time is 1 to 4 h, the heating rate during the calcination process is 2 to 10 °C / min, and the calcination temperature is 400 to 900 °C.
[0016] Preferably, in step 3, the water leaching duration of the composite material is 10 to 30 min.
[0017] Preferably, in step 4, the sodium source is sodium carbonate, and the ratio of the raw material to the sodium source is 0.8 to 1.2.
[0018] Preferably, in step 4, the manganese source is manganese dioxide, and the addition amount is to adjust the nickel-manganese ratio to 0.8 to 1.
[0019] Preferably, in step 4, the molar ratio of SiO2 / B2O3 in the silicon borate ranges from 1 to 1.5, the coating amount is 3% to 15% of the transition metal oxide, and the thickness of the coating layer is 10 to 50 mm.
[0020] Preferably, in step 4, the ball-milling time is 1 to 12 h, and the ball-milling speed is 100 - 800 rpm.
[0021] Preferably, in step 5, the molecular formula of the regenerated layered cathode material is Na a Li b Ni c Co d Mn e O2@Me2O·B2O3·nSiO2, where Na a Li b Ni c Co d Mne O2 is the active main body, and Me2O·B2O3·nSiO2 is the coating layer. Among them, 0.8 ≤ a ≤ 1, 0.01 ≤ b ≤ 0.03, c + d + e = 1, 1 ≤ n ≤ 1.5, and Me is one or more of Na, Mn, Co, and Ni.
[0022] Preferably, the calcination time in step 4 is 9 - 15 h, the heating rate during the calcination process is 2 - 10 °C / min, and the calcination temperature is 700 - 900 °C.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The cathode material of waste nickel - cobalt - manganese ternary lithium - ion batteries is directly recycled to prepare a high - performance sodium - ion battery cathode material with silicon - borate coating modification. The recycling process is greatly reduced, avoiding the acid - leaching dissolution process, and the whole process is a solid - solid transformation. It has significant environmental and economic benefits.
[0025] (2) During the sintering process, borosilicate forms a glassy substance with good fluidity due to high - temperature melting, which can uniformly coat the surface of the sodium - ion cathode material to form a homogeneous solid solution. This dynamic coating mechanism effectively reduces the material interface defects, improves the bonding strength between the coating layer and the matrix, and thus significantly enhances the structural stability of the cathode material. At the same time, the fluid characteristics enable the coating layer to adapt to the volume change of the material, extending the cycle life of the battery.
[0026] (3) The introduction of silicon element forms a borosilicate composite network, greatly improving the thermal stability and mechanical strength of the coating layer, while optimizing the sodium - ion diffusion kinetics. The high chemical inertness of silicon can effectively isolate the erosion of the electrolyte on the active material, and the synergistic effect of silicon - oxygen (Si - O) and boron - oxygen (B - O) bonds further strengthens the ion - sieving ability of the coating layer, reducing the dissolution of transition metals. In addition, the light - weight property of silicon reduces the mass ratio of the coating layer, improving the tap density of the material while maintaining a high specific capacity, providing a new idea for the design of high - energy - density sodium - ion batteries. Description of the Drawings
[0027] Figure 1 It is a test chart of the electrochemical performance of the regenerated material coated with silicon borate.
[0028] Figure 2 It is a test chart of the electrochemical performance of the regenerated material without silicon borate coating. Detailed Embodiments
[0029] The present invention will be further described below in conjunction with embodiments.
[0030] Embodiment 1
[0031] This embodiment provides a method for directly regenerating a silicon borate-coated modified sodium-ion battery cathode material from a waste ternary lithium-ion battery cathode material:
[0032] (1) Take 5 g of waste ternary cathode powder and 3 g of ammonium sulfate, add them to a ball milling jar, put it into a ball mill, and grind at a rotation speed of 600 r / min for 6 h to obtain a uniformly mixed powder material.
[0033] (2) Take 5 g of the powder and put it into a small porcelain boat, and place it in the middle part of the tube furnace. Under an Ar / N2 atmosphere, heat it to 700 °C at a heating rate of 5 °C / min and hold for 1 h.
[0034] (3) Put the obtained composite material into a beaker, add 500 mL of deionized water at the same time, extract part of the Li, after treating it under ultrasonic conditions for 10 min, carry out suction filtration, and dry the filter cake in an oven at 100 °C to obtain a transition metal oxide solid.
[0035] (4) Conduct ICP testing on the transition metal oxide solid to determine the content of each element, mix in an appropriate amount of manganese oxide to adjust the nickel-manganese ratio to 1:1, and take Na2O·B2O3·SiO2 according to the molar ratio of the transition metal oxide to sodium carbonate of 1:1.1, with the coating amount taken as 5% of the precursor, mix and add them to the ball milling jar, put it into the ball mill, and grind at a rotation speed of 400 r / min for 10 h to obtain a uniformly mixed powder material.
[0036] (5) Take 5 g of the powder and put it into a small porcelain boat, and place it in the middle part of the muffle furnace. Heat it to 800 °C at a heating rate of 3 °C / min and hold for 12 h to obtain the cathode material NaLi 0.01 Ni 0.44 Co 0.12 Mn 0.44 O2@Na2O·B2O3·SiO2.
[0037] (6) Conduct electrochemical performance testing at room temperature. The results show ( Figure 1 ), the initial discharge specific capacity is 123.5 mAh g -1 , and the retention rate remains 89% after 100 cycles, showing high specific capacity and good cycle stability.
[0038] Example 2
[0039] This embodiment provides a method for directly regenerating a modified sodium-ion battery cathode material with silicon borate coating from a waste ternary lithium-ion battery cathode material. The preparation method includes the following steps:
[0040] (1) Take 7 g of waste ternary cathode powder and 4 g of ammonium sulfate and add them to a ball milling jar. Place the jar in a ball mill and mill at a rotation speed of 400 r / min for 8 h to obtain a uniformly mixed powder material.
[0041] (2) Take 5 g of the powder material and place it in a small porcelain boat. Then place the boat in the middle part of the tube furnace. Under an Ar / N2 atmosphere, heat it at a heating rate of 3 °C / min to 800 °C and hold for 2 h.
[0042] (3) Put the obtained composite material into a beaker, and at the same time add 500 mL of deionized water to extract Li. After treating it under ultrasonic conditions for 20 min, perform suction filtration. The filter cake is dried in an oven at 120 °C to obtain a transition metal oxide solid.
[0043] (4) Perform ICP testing on the transition metal oxide solid to determine the content of each element. Mix in an appropriate amount of manganese oxide to adjust the nickel-manganese ratio to 0.95:1. Then, take Na2O·B2O3·SiO2 in a molar ratio of 1:1.1 with the transition metal oxide and a coating amount of 5% of the precursor. Mix them and add them to a ball milling jar. Place the jar in a ball mill and mill at a rotation speed of 400 r / min for 10 h to obtain a uniformly mixed powder material.
[0044] (5) Take 5 g of the powder material and place it in a small porcelain boat. Then place the boat in the middle part of the muffle furnace. Heat it at a heating rate of 5 °C / min to 850 °C and hold for 16 h to obtain the cathode material Na 0.01 Ni 0.44 Co 0.12 Mn 0.44 O2@Na2O·B2O3·SiO2.
[0045] Comparative Example 1
[0046] This comparative example provides a method for directly regenerating the cathode material of a sodium-ion battery from the cathode material of a waste ternary lithium-ion battery, which does not involve coating treatment. The composition of the cathode material is Na 1.1 Li 0.01 Ni 0.44 Co 0.12 Mn 0.44 O2, and the preparation method includes the following steps:
[0047] (1) Take 5 g of waste ternary cathode powder and 3 g of ammonium sulfate and add them to a ball milling jar. Place the jar in a ball mill and mill at a rotation speed of 600 r / min for 6 h to obtain a uniformly mixed powder material.
[0048] (2) Take 5 g of the powder material and place it in a small porcelain boat. Then place the boat in the middle part of the tube furnace. Under an Ar / N2 atmosphere, heat it at a heating rate of 5 °C / min to 800 °C and hold for 1 h.
[0049] (3) Put the obtained composite material into a beaker, and at the same time add 500 mL of deionized water to extract part of the Li. After treating it under ultrasonic conditions for 10 min, carry out suction filtration, and dry the filter cake in an oven at 100 °C to obtain a transition metal oxide solid.
[0050] (4) Conduct ICP testing on the transition metal oxide solid to determine the content of each element, mix in an appropriate amount of manganese oxide to adjust the nickel-manganese ratio to 1:1, and add the transition metal oxide and sodium carbonate into a ball milling jar according to a molar ratio of 1:1.1, put it into a ball mill, and grind it at a rotation speed of 400 r / min for 10 h to obtain a uniformly mixed powder material.
[0051] (5) Take 5 g of the powder material and put it into a small porcelain boat, and place it in the middle part of a muffle furnace. Heat it up to 800 °C at a heating rate of 3 °C / min and keep it for 12 h to obtain the cathode material Na 1.1 Li 0.01 Ni 0.44 Co 0.12 Mn 0.44 O2.
[0052] (6) Conduct electrochemical performance testing at room temperature. The results show ( Figure 2 ), the initial discharge specific capacity is 122.9 mAh g -1 , after 100 cycles, the retention rate is 80.56%, showing poor cycle performance.
[0053] The applicant declares that the above description is only the specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and the disclosure scope of the present invention.
Claims
1. A method for preparing a sodium-ion battery cathode material coated and modified with silicate borate using waste ternary cathode materials, characterized in that, It includes the following steps: (1) Mix the waste nickel-cobalt-manganese ternary cathode and ammonium sulfate in a certain proportion and carry out mechanical ball milling to achieve uniform compounding; (2) Carry out high-temperature calcination in a tube furnace to obtain a composite material; (3) Carry out selective water leaching of lithium from the composite material. After drying the leaching residue, a transition metal oxide containing a small amount of remaining lithium is obtained; (4) Mix the precursor with a manganese source, a sodium source, and a silicon borate in a certain proportion, and then carry out mechanical ball milling for sufficient mixing; (5) Place it in a muffle furnace for solid-phase sintering to obtain a sodium-ion layered cathode material.
2. A method for preparing a sodium-ion battery cathode material coated and modified with silicate borate using waste ternary cathode material, characterized in that, The molecular formula of the nickel-cobalt-manganese ternary material precursor is Ni 1-x-y Co x Mn y O2, where 0.1 ≤ x ≤ 0.3 and 0.1 ≤ y ≤ 0.3; the silicate is Me2O·B2O3·nSiO2, where 1 ≤ n ≤ 1.5, and Me is one or more of Na, Mn, Co, and Ni, preferably Me is Na. The molecular formula of the regenerated layered cathode material is Na a Li b Ni c Co d Mn e O2@Me2O·B2O3·nSiO2, where 0.8 ≤ a ≤ 1, 0.01 ≤ b ≤ 0.03, c + d + e = 1, 1 ≤ n ≤ 1.5, and Me is one or more of Na, Mn, Co, and Ni.
3. The method for preparing a sodium-ion battery cathode material coated and modified with silicate borate by using waste ternary cathode material according to claims 1-2, characterized in that, In step 2, the mass ratio of the waste cathode to ammonium sulfate is 1:0.5 - 1:0.
7.
4. A method for preparing a sodium battery cathode material coated and modified with silicate borate by using waste ternary cathode materials according to claims 1-3, characterized in that, In step 2, the ball milling time is 1 - 24 h, and the ball milling speed is 100 - 800 rpm.
5. A method for preparing a sodium battery cathode material coated and modified with borosilicate by using waste ternary cathode materials according to claims 1-4, characterized in that, In step 3, the atmosphere in the tube furnace is Ar / N2 or N2.
6. A method for preparing a sodium-ion battery cathode material coated and modified with silicate borate by using waste ternary cathode material according to claims 1-5, characterized in that, In step 3, the calcination time is 1 - 4 h, the heating rate during the calcination process is 2 - 10 °C / min, and the calcination temperature is 400 - 900 °C.
7. A method for preparing a sodium-ion battery cathode material coated and modified with borosilicate by using waste ternary cathode materials according to claims 1-6, characterized in that, In step 4, the ultrasonic water leaching time is 10 - 30 min.
8. A method for preparing a sodium-ion battery cathode material coated and modified with silicate borate by using waste ternary cathode material according to claims 1-7, characterized in that, In step 5, the manganese source is manganese dioxide, and the addition amount is to adjust the nickel-manganese ratio to 0.8 - 1; the sodium source is sodium carbonate, and the ratio of the raw material to the sodium source is 0.8 - 1.2; the molar ratio of SiO2 / B2O3 in the silicon borate is between 1 - 1.5, the coating amount is 3% - 15% of the transition metal oxide, and the thickness of the coating layer is 10 - 50 mm.
9. A method for preparing a sodium-ion battery cathode material coated and modified with silicate borate by using waste ternary cathode materials according to claims 1-8, characterized in that, In step 5, the ball milling time is 1 - 12 h, and the ball milling speed is 100 - 800 rpm.
10. A method for preparing a sodium-ion battery cathode material coated and modified with silicate borate by using waste ternary cathode materials according to claims 1-9, characterized in that, In step 4, the calcination time is 9 - 15 h, the heating rate during the calcination process is 2 - 10 °C / min, and the calcination temperature is 700 - 900 °C.
Citation Information
Cited By
Method for modifying and repairing waste lithium iron phosphate positive electrode material by using tetrabutyl silicate and application of method in deep sea field
CN122315124A